Lithospermic acid, a novel KLK5 inhibitor, ameliorates rosacea by suppressing the TLR4/NF-κB signaling pathway and rectifying phenylalanine metabolism - Xu, Jingang; Wang, Xinyu; Chen, Manyu; Xu, Boya; Zhang, Tingting; Zhang, Yao; Xu, Yueye; Guo, Junjie; Xu, Jingyun; Li, Yuanyuan; Zhao, Jinhong; Zhou, Hongming (Frontiers in Immunology, 2026)
BackgroundRosacea is a chronic inflammatory skin disease, with LL-37 driving inflammation. Inhibiting serine protease kallikrein-5 (KLK5) overactivity can reduce LL-37 production, thereby relieving this inflammation. Lithospermic acid (LA), a plant-derived synthetic phenolic carboxylic acid, is known for its potent anti-inflammatory and antioxidant effects. However, its effects on rosacea remain unelucidated. This study aimed to investigate the KLK5-inhibiting activity of LA to assess its therapeutic efficacy in rosacea management, along with identifying its underlying mechanisms.MethodsHerein, molecular docking and dynamic simulations of LA–KLK5 were performed via virtual screening. A rosacea mouse model was established by injecting LL-37. The therapeutic efficacy of LA was assessed based on skin erythema scores and pathological analysis (hematoxylin–eosin and toluidine blue staining). Enzyme-linked immunosorbent assay, reverse transcription-quantitative polymerase chain reaction, immunofluorescence, and Western blotting were employed to quantify relevant gene and protein expression in serum and back skin. Untargeted metabolomics was used to profile alterations in serum metabolites.ResultsNotably, LA was identified as a high-affinity KLK5 inhibitor and interacted through hydrophobic and hydrogen bonds, forming a stable complex with KLK5. Furthermore, LA significantly reduced pathological changes in the skin of rosacea-affected mice, along with inhibiting the expression of matrix metalloproteinase (MMP)-9, cluster of differentiation (CD)31, CD4+, and KLK5-associated proteins in the skin tissues. Pro-inflammatory cytokines (interleukin [IL]-1β, IL-6, and tumor necrosis factor [TNF]-α) in serum and the activation of skin Toll-like receptor (TLR)2, MMP-9, KLK5, IL-1β, IL-6, and TNF-α genes were also suppressed. Additionally, LA inhibited TLR4/nuclear factor (NF)-κB-regulated inflammation by binding to KLK5, thereby improving rosacea. Metabolomics analysis identified 44 dysregulated metabolites in diseased mice, of which 28 were restored to near-normal levels following LA treatment. Pathway enrichment revealed phenylalanine metabolism regulation as a central mechanism of action of LA.ConclusionsOverall, this study, for the first time, shows that LA is a novel KLK5 inhibitor, as confirmed by molecular docking and kinetic modelling. Additionally, the results highlight that LA can ameliorate rosacea-like dermatitis through dual inhibition of KLK5 and TLR4/NF−κB signaling, while correcting metabolic disturbances, especially in phenylalanine metabolism.